Pengaruh Pestisida Nabati Limbah Batang Tembakau Virginia terhadap Serangan Hama Pengisap Daun (Thrips Palmi) Pada Tanaman Kentang (Solanum tuberosum L.) - Adhia Nirmala, Wiwin; Sarjan, Muhammad; Haryanto, Hery (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aims to determine the effect of several concentrations of botanical pestisides from virginia tobacco stem waste to the leaf-sucking pests (Thrips palmi) on potato plants. This exteriment was carried out from August to November 2020 in Sembalun Bumbung Village, Sembalun District, East Lombok Regency, West Nusa Tenggara. The method use in this study is an experimental method with field experiments and the design used is a Rendomized Block Design (RBD) with 6 treatments, P0 (control), P1 (abamectin), P2 (botanical pesticide of Virginia tobacco stem waste 2 ml/L), P3 (botanical pesticide of Virginia tobacco stem waste 4 ml/L), P4 (botanical pesticide of Virginia tobacco stem waste 6 ml/L) and P5 (botanical pesticide of Virginia tobacco stem waste 8 ml/L). each treatment had 3 replications so that 18 experimental plots were obtained. The result showed that the concentration of Virginia tobacco stem pesticide was more effective in controlling the populations of Thrips palmi than other Virginia tobacco stem pesticide concetrations. However, the Virginia tobacco stem waste botanical pesticide was not effective on controlling the intensity of T. palmi